An investigation of avoidance by Antarctic krill of RRS James Clark Ross using the Autosub-2 autonomous underwater vehicle - Brierley, Andrew Stuart; Fernandes, PG; Brandon, MA; Armstrong, F; Millard, NW; McPhail, SD; Stevenson, P; Pebody, M; Perrett, J; Squires, M; Bone, DG; Griffiths, G (2003)
The autonomous underwater vehicle (AUV) Autosub-2 was deployed on eight missions ahead of RRS James Clark Ross in the northern Weddell Sea and in the Bransfield Strait, Southern Ocean, to assess avoidance of the research vessel by Antarctic krill Euphausia superba. The AUV was equipped with the same type of scientific echosounder as the research vessel (Simrad EK500 operating at 38 and 120 kHz) and measured the density of krill along transect acoustically (g m(-2) wet mass) prior to the ship's arrival. We hypothesised that if krill avoided the ship, perhaps in response to radiated noise, then the ship should detect less krill than the AUV which is known to have much lower noise levels than the ship. We were unable to detect any significant difference between the density of krill detected by the ship or the AUV, either at the transect level or at finer scales within transects. We conclude, therefore, that avoidance by krill of RRS James Clark Ross will not significantly bias acoustic estimates of krill abundance by this vessel. (C) 2002 Elsevier Science B.V. All rights reserved.